Laparoscopy in diagnostics of pelvic pain - Makowska, Justyna; Sochaj, Marta; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
Objectives: The objective was to evaluate the usefulness of laparoscopy in the diagnosis of pelvic pain and to verify whether diseases diagnosed by laparoscopy correlate with age or body mass index of operated women. Materials and Methods: This study is a retrospective analysis of 193 charts of patients who underwent laparoscopy during 2001-2005 in the Department of Gynaecological Surgery and Laparoscopy in the Polish Mother’s Memorial Research Institute. Two divisions into four groups of patients were made, according to age: n = 49 aged 20-26 years, n = 48 aged 27-30 years, n = 48 aged 31-37 years and n = 48 aged 38-59 years and according to BMI: n = 49, BMI 15.8-20 kg/m 2 , n = 48, BMI 20.0-22.3 kg/m 2 , n = 48, BMI 25-40.9 kg/m 2 . The logistic regression test was applied. Results: The most frequent diagnosed pathologies in all groups were: endometriosis (n = 125, 64.7%), adhesions (n = 77, 39.8%) and ovarian cysts (n = 32, 16.5%). Among women between 20 and 30 years old, the most frequent diagnosis was endometriosis (p = 0.016), the second adhesions (p = 0.035). With every year of life the risk of finding endometriosis decreases by 4.2% and the risk of finding adhesions increases by 3.7%. Conclusions: Laparoscopy is an important diagnostic procedure to diagnose the most frequent pathologies responsible for pelvic pain such as endometriosis, adhesions, ovarian cysts, pelvic inflammatory disease, and uterine myomas.